Fabrication of near-net-shaped reaction-bonded silicon carbide tubes by thermoset molding and reaction infiltration of silicon melt - Jun, HW; Lee, HW; Song, H; Shin, H; Kim, J; Ha, J (KOREAN ASSOC CRYSTAL GROWTH, INC, 2002)
A reaction-bonded silicon carbide tube has been fabricated by a thermoset molding (transfer molding) technique using a mixture of thermoplastic and thermosetting polymer resins. Shrinkage and stress development during the centrifugal thermoset molding have been minimized by tailoring the particle packing characteristics with a multimodal particle size distribution. Debinding behavior was optimized in a two-step process consisting of the capillary migration of the thermoplastic resin and subsequent thermal pyrolysis of the thermosetting resin. Reactive infiltration of the silicon melt was carried out in a vacuum or inert atmosphere, during which liquid agglomeration of the silicon melt by surface tension was prevented by insitu formation of a silicon carbide cage structure.
Keywords: MICROSTRUCTURE; COMPOSITES